Wellness experiences and their impact on spa guests’ well-being in Cameron Highlands - Wan Daud, Wan Nur Izzah Athirah; Aluwi, Nurul Najihah; Muhammad Ghazali, Ameleya; Zulkurnain, Muhammad Zulhilmi; Mohd Nawi, Mohd Zulfakar (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Wellness tourism has emerged as a rapidly growing segment of the global travel industry, yet limited scholarly attention has been given to its influence on guests’ emotional and psychological well-being in Malaysia. This study examines how four dimensions of wellness experiences, which are education, entertainment, aesthetics, and escapism, shape the hedonic well-being of spa visitors in Cameron Highlands. Addressing a gap in the literature on the mental and emotional outcomes of spa experiences, the research employed stratified sampling to survey 370 guests across five spas. Data were analysed using SEM to identify the experiential elements most strongly associated with enhanced joy and satisfaction. The findings provide actionable insights for spa operators and tourism policymakers, highlighting strategies to enrich guest experiences and improve service delivery. By linking wellness experiences to hedonic well-being, the study contributes to advancing service innovation and supporting the sustainable growth of wellness tourism in Malaysia.